(untitled) (Materiali di Estetica. Terza serie, 2024)
This article presents a poignant collection of poems by Federica Schiaffino, reflecting on themes of waiting, loss, solitude, and the ineffable nature of love. Schiaffino, an accomplished figure from Genoa, Italy, combines her experiences in cultural projects, historical consultation, and local politics with deeply personal reflections, particularly highlighted in her poetry written during periods of significant personal grief and reflection. The text traverses various moments—from the anticipation of love to the solemn contemplation of mortality—illustrated through vivid imagery of natural elements and quiet urban settings. The poems, marked by a delicate balance between the existential and the intimate, offer a meditation on human fragility and the transcendent moments that shape our understanding of destiny and connection.